(3GdENQGL GdUMaj GdEdcJQhfj (B:s (3Odjd GdeNQL GdUMaj dEHOGY GdUaMGJ HGSJNOGe GdMGSH GdCdj h HQGeL GdahJhThH(B, (3h GdchGQc GcS HQS (B/s - (3MSfjf, Tajbs ([(3Ohf ecGf(B] :s [(3Ohf fGTQ(B] (3,s, 2007)
(3jMJhj GdcJGH Ydi (B8 (3aUhd GdaUd GdGhd jJMOK Yf dZI GdJUeje h GdENQGL GdUMaj GdaUd GdKGfj(B: (3GdhSGFd GdEdcJQhfjI aj GdENQGL GdUMaj GdEdcJQhfj GdaUd GdKGdK(B: (3ENQGL GdeJf HGSJNOGe GdMGSH GdaUd GdQGHY(B: (3GdUhQ aj GdENQGL GdUMaj GdEdcJQhfj GdaUd GdNGeS(B: (3CSS h eaGgje Gddhf ddeTJZdjf HGdJUeje(B- (3GdaUd GdSGOS(B: (3GdCfXeI GdEdcJQhfjI dJUeje GdUaMGJ(B- (3GdaUd GdSGHY(B: (3eYGdLI GdUhQ HHQfGGeL GdahJhThH (BCS (3GdaUd GdKGef(B: (3fUGFM GdNHQGA fMh JUeje GdcJQhfj LjOs
(3HHdjhZQGajG (B: (3U(B.347-351s
Keywords: (3GdENQGL GdUMaj GdEdcJQhfjs; (3GdENQGL GdUMajs; (3HQGeL GdahJhThHs; (3dUMGaIs